2016
DOI: 10.1016/j.celrep.2016.04.034
|View full text |Cite
|
Sign up to set email alerts
|

Direct Upregulation of STAT3 by MicroRNA-551b-3p Deregulates Growth and Metastasis of Ovarian Cancer

Abstract: SUMMARY 3q26.2 amplification in high-grade serous ovarian cancer leads to increased expression of mature microRNA miR551b-3p, which is associated with poor clinical outcome. Importantly, miR551b-3p contributes to resistance to apoptosis and increased survival and proliferation of cancer cells in vitro and in vivo. miR551b-3p up-regulates STAT3 protein levels with STAT3 being required for the effects of miR551b-3p on cell proliferation. Rather than decreasing levels of target mRNA as expected, we demonstrate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 32 publications
2
58
0
Order By: Relevance
“…miRNAs in the nucleus have been shown to act at the promoter level affecting transcription. For example, miR-551b-3p directly upregulates STAT3 expression by binding to a complementary sequence on the STAT3 promoter, and recruiting RNA polymerase II and the TWIST1 transcription factor to activate STAT3 transcription (Chaluvally-Raghavan et al, 2016). miRNAs have also been detected in membrane-bound compartments, such as secreted vesicles (Zhang et al, 2010) and mitochondria (Das et al, 2012).…”
Section: Mirna Biogenesis and Mechanism Of Actionmentioning
confidence: 99%
“…miRNAs in the nucleus have been shown to act at the promoter level affecting transcription. For example, miR-551b-3p directly upregulates STAT3 expression by binding to a complementary sequence on the STAT3 promoter, and recruiting RNA polymerase II and the TWIST1 transcription factor to activate STAT3 transcription (Chaluvally-Raghavan et al, 2016). miRNAs have also been detected in membrane-bound compartments, such as secreted vesicles (Zhang et al, 2010) and mitochondria (Das et al, 2012).…”
Section: Mirna Biogenesis and Mechanism Of Actionmentioning
confidence: 99%
“…Interestingly, miR-551-3p binds to the promoter of signal transducer and activator of transcription 3 (STAT3), leading to increased expression of STAT3. Treatment of mouse models with anti-miR-551b-3p via a liposomal delivery system decreased tumor burden in vivo (69). These few pre-clinical models show promise for treatment of EOC with molecules that regulate microRNA expression.…”
Section: Microrna Molecules As Therapy For Eocmentioning
confidence: 99%
“…Previous study showed that STAT3 was upregulated in CC and promoted tumor growth, invasion and metastasis 33. Furthermore, microRNA-551-3p contributed to resistance to apoptosis and increased survival and proliferation of ovarian cancer cells by activating STAT3 transcription 34. A recent study demonstrated that STAT3, an important oncogene in human cancer, was a bona fide target of BCL3 in CC cell line 21.…”
Section: Discussionmentioning
confidence: 99%